Outcomes Of Early Cholecystectomy In Acute Cholecystitis: Prospective 10-Year Experience In A Private Sector Tertiary Care Hospital In Sri Lanka - Abeysuriya, Vasitha; Chandrasena, Lal (Journal of Society of Surgeons of Nepal, 2024)
Introduction: The consensuses of Laparoscopic cholecystectomy (LC) as the treatment of choice in acute cholecystitis (AC) is well agreed upon. The aim of this prospective study was to assess the outcomes of early cholecystectomy (EC), from the first appearance of symptoms in patients diagnosed with AC. Methods: Data were collected through a computer-based health information system from a private sector tertiary care, Nawaloka Hospital, Colombo, Sri Lanka from 2013 to 2023. The data of 255 patients who had AC and underwent EC were analysed. AC was diagnosed by clinical, laboratory, and radiological parameters. Standard four port laparoscopic technique was used. Operative findings of the gallbladders were recorded as described by Noiret al. Sakuramoto classification was used to record histopathology. The data were evaluated with respect to demographics, duration of hospital stay, duration of operation, adhesion score, conversion rates, morbidity and mortality. All patients were consented during their admission to have their data for research purposes while maintain strict confidentiality. The Ethical clearance was obtained. Results: The majority were females (73%). The mean age of males was 45±4.6 years and 43±4.7 years in females. The mean time from symptom onset to operation was 32±3.4 hours. The mean duration of operation was 60±6.7 minutes. Majority had mild (36%) to moderate (54%) adhesion scores. The rate of conversion was 3.6%. Average duration of hospital stay was 2.9±1.1 days. No patient had significant morbidity or mortality. Majority of the bile cultures revealed Enterobacter spp. Most of the histopathology revealed mild to moderate AC. Conclusion: Our study showed that EC results in with a shorter duration of operation and hospital stay and lower rates of conversion. Furthermore, there were no significant morbidity or mortality.